HEALTH FINANCING PLANNING IN HOSPITAL - Michelle Angelika S; Handar Subhandi Bakhtiar (Jurnal Medika Hutama, 2022)
Health financing is a factor that significantly affects the health quality of a country. Problems arising from health financing include a lack of funds and an increase in funds. This paper used a literature review as the method. The purpose of this scientific paper was to increase awareness about health financing in hospitals. Thus, this paper is expected to be useful in building financing plans to optimize health services. From various research articles, it can be concluded that the importance of health financing is used as a reference for targets that hospital activities in the future must achieve. The need for synchronization between one policy and another, starting from planning documents to budgeting. There is a strong relationship between the hospital institutional status and health financing pattern.